Implementation of Removal of Heavy Damaged Regional Goods in DIY Education and Training Agency - Wandi, Wandi; Wening, Nur; Handayani, Sri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Implementation of Elimination of Heavily Damaged Area Property at the DIY Education and Training Agency. This research aims to determine the implementation of the elimination of heavily damaged BMD at the DIY Education and Training Agency based on Ministry of Home Affairs Regulation No. 19 of 2016. The process for eliminating BMD is based on Permendagri No. 19 of 2016 changed the mechanism when compared to the previous regulation. Based on research results, it shows that the process of eliminating BMD is seriously damaged at the DIY Education and Training Agency, its implementation is still focused on the DIY Financial and Asset Management Agency (BPKAD) as the leading sector for BMD management. The main obstacles that become obstacles are the incomplete documentation and the physical obscurity of the goods proposed for disposal. This was caused by several things, namely the grant process in the past which was not accompanied by documentation, inadequate supervision of heavily damaged BMD, inadequate Human Resources (HR), and the absence of Standard Operating Procedures (SOP) regarding the removal of BMD.